'A question of survival': Canada and the Rapacki Plan for the denuclearisation of Central Europe, 1957–59. Issue 4 (2nd October 2021) - Musto, Ryan A.
ABSTRACT: In October 1957, Poland proposed the Rapacki Plan for the denuclearisation of Central Europe. While North Atlantic Treaty Organization (NATO) members attacked the initiative, Canada viewed it as a means to ease Cold War tensions. Although Canada joined with its allies to reject the Plan, it embarked on a quest for counterproposals to restrain NATO nuclear sharing and reduce the chances of nuclear war. Canada's efforts alarmed Western allies and helped lead to a second Rapacki Plan. Overall, this article details Canada's struggle to assert itself as a middle power and provides a robust example of Western interest in the Rapacki Plan.